Pelatihan Teknis Pembuatan KIT Praktikum Listrik Dinamis sebagai Sarana Penunjang Pembelajaran Fisika di SMA Boarding School Putra Harapan Purwokerto - Muhammad Sehah (Universitas Jenderal Soedirman, 2023)
Technical training activities for manufacturing Integrated Instrument Components (IIC) for Dynamic Electrical Practice as a means of supporting Physics learning at SMA Boarding School Putra Harapan Purwokerto have been carried out. The aim of the activity is to provide technical training for Physics teachers and students at SMA Boarding School Putra Harapan so they can design and realize the IIC for Dynamic Electrical Practice. The expected benefit is the increased ability and skills of teachers and students in designing and realizing IIC for the Dynamic Electrical Practice from materials that are easily available on the market. After the technical training and the realization of IIC for the Dynamic Electrical Practice, then observations were made using a questionnaire. The observation results show that most of the participants gave a positive response to the technical training activities. This is shown from the average achievement of the activity success of 79.40%; with the highest achievement of 89.66% in the form of support for providing a set of IIC for Dynamic Electrical Practice from the Community Service Team to SMA Boarding School Putra Harapan; as well as the lowest achievement of 66.67% in the form of a willingness to independently realize the IIC for Physics practice. The factors that hinder this activity are the absence of a laboratory that supports the implementation of practice activities for students and the lack of skills of teachers in realizing IIC for the Physics Practice